História em quadrinhos nas pesquisas sobre história para o ensino de matemática (1990-2018) - SILVA NETO, Benjamim Cardoso da (Universidade Federal de Mato Grosso, 2022)
This article aims to identify and describe researches about history for the teaching of mathematics, that combine history of mathematics to history in comics by means of breeding strategies of didactic proposals that connect to mathematical knowledge, in a playful manner, in promoting an improvement of teaching and apprenticeship of this discipline. Thus, we find two searches of professional master's dissertations that were used of the story resource in comics, associated with the history of mathematics, for teaching areas of plane figures, volumes of solids geometric and equations 2nd grade. Some others works were derived of these searches of dissertations, beyond the products educational created as a requirement of professionals master's degree. Such research make us realize a movement still weak of productions that derive from them, and express exemplary contributions and potentialities for use per parts from other professionals of basic education, of Teacher Education of math and also serve of research source, that is what happens with this work, that makes it public, about everything, productions that directed to the use of the history of mathematics in the classroom.